PENGARUH PENDIDIKAN DAN PELATIHAN TERHADAP PRESTASI KERJA KARYAWAN DI PT.TELEKOMUNIKASI INDONESIA (TELKOM) REGIONAL VII GORONTALO - Nadila Septiani Putri; Andi Yusniar Mendo; Agus Hakri Bokingo (STIE Kertanegara Malang, 2019)
This study aims to determine how much influence Education and Training on Employee Performance at PT. Indonesian Telecommunications (Telkom) Regional VII Gorontalo. The sample in this study were 67 people. Then the data analysis uses simple linear regression with the help of SPSS version 22. The results of the study show that the coefficient of determination R2 is 0.406. This value means that 40.6% of Work Achievement at PT. Telekomunikasi Indonesia (Telkom) Gorontalo Regional VII is influenced by the Education and Training program conducted by the company. The influence of other variables on employee performance is 59.4%. Keywords: Education and Training, employee work performance.